Iridium-Catalyzed Direct Amidation of Imidazoles at the C-2 Position with Isocyanates in the Presence of Hydrosilanes Leading to Imidazole-2-Carboxamides - Fukumoto, Yoshiya; Shiratani, Motohiro; Noguchi, Hikaru; Chatani, Naoto (Synthesis, 2021)
Regioselective coupling reaction of N-substituted imidazoles with isocyanates in the presence of a stoichiometric amount of hydrosilanes catalyzed by Ir4(CO)12 to give imidazole-2-carboxamides is reported. Imidazoles bearing an (O-silyl)carboximidate group at the 2-position appear to be initially formed in the reaction; these are then hydrolyzed to the final products in situ. The addition of the hydrosilane was essential for the catalytic reaction to proceed. Substituents on the imidazole ring had no effect on the reaction, except for certain bulky substituents such as tBu and Ph groups at the 4-position. Triazoles such as 4-methyl-4H-1,2,4-triazole and 1-methyl-1H-1,2,4-triazole were also applicable to this C–H amidation, and the latter reaction proceeded regioselectively at the carbon atom between the sp3 and sp2 nitrogen atoms of the ring, and not between the two sp2 nitrogen atoms.
Keywords: C–H bond functionalization; imidazoles; isocyanates; hydrosilanes; iridium catalysis; imidazole 2-carboxamides